The effectiveness of literature circles on ESL students comprehension of a graphic novel - Ho, Lai Ying (Universiti Pendidikan Sultan Idris, 2018)
The effectiveness of literature circles on ESL students comprehension of a graphic novel by Ho, Lai Ying